Chemical compositium of essential oil from Caesalpinia spinosa “tara”, antioxidant evaluation and antibacterial effect against Streptococcus mutans - Castro, Américo J. (2017)
Was determinated chemical composition of essential oil from Caesalpinia spinosa, obtained by stripping with steam method, with a yield of 0,125% v/w, as well as its antioxidant capacity and antibacterial effect against Streptococcus mutans ATCC 35668. To identify chemical constituents were employed Gas Chromatography and Mass Spectrometry (GC/MS), finding 23 compounds, being in greater quantity: pelargonaldehído (11,21%); dihydro-neoclovene-(i) (5,51%); naphthalene,1,2,3,5,6,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl)-,(15-CIS)- (4,87%) y dihydro-cis-alfa-copaene-8-ol (4,13%). Evaluation of antioxidant activity was performed using the methods of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and acid radical 2,2'-azino-bis- (3-etilbenzotiazolin-6-sulfonic acid) (ABTS⁺), determining that IC50 to both methods was > 200 µL/mL, using as captation reference trolox®, which had IC50 3,8 µg/mL. The determination of antibacterial effect was made by agar diffusion method, where 100, 50 and 25% tara oil concentrations, produced inhibition halos of 21, 18 and 16 mm, respectively, against Streptococcus mutans, being negative control ethanol 96º and positive control ciprofloxacin, which presented a halo of 25 mm. Were concluded that the chemical composition of the essential oil obtained from Caesalpinia spinosa has antioxidant activity, although is not significant compared to the reference compound Trolox®, while its antibacterial activity at used concentrations had significant results.